Occupation and risk of stomach cancer in Poland. Issue 5 (18th April 2005) - Krstev, S; Dosemeci, M; Lissowska, J; Chow, W-H; Zatonski, W; Ward, M H
Abstract : Background: In spite of the dramatic decline in the incidence of stomach cancer in the twentieth century, Poland has one of the highest rates in the world. Aims: To evaluate the risk of stomach cancer by grouped occupations and industries, as well as by some specific occupational exposures. Methods: Cases (n = 443) were newly diagnosed with stomach adenocarcinomas between 1994 and 1996. Controls (n = 479) were randomly selected from the general population in Warsaw. Results: Only a few occupations and industries were associated with significantly increased risks of stomach cancer. The most suggestive finding was for work in the leather goods industry. Risk was also significantly increased among men working in fabricated metal production and among women ever employed as managers and governmental officials. Men ever employed as teaching professionals and women employed as technical and science professionals had significantly decreased risks of stomach cancer. Among men, a significant positive trend in risk with duration of employment was observed for work in the leather industry and special trade construction. No significantly increased risks were observed for specific exposures assessed by a job-exposure matrix or by self-reports. However among men there were non-significantly increased risks with 10 or more years exposure to asbestos, metal dust, and nitrosamines assessed by a job-exposure matrix. Conclusions: Employment in the leather goods industry, special trade construction, and metal fabrication was associated with an increased risk of stomach cancer among men. However, there were only weak associations with specific exposures. Occupational exposures do not contribute substantially to the high rates of stomach cancer in Poland.